1976
DOI: 10.1007/bf00397183
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen isotope discrimination in higher plants: Correlations with photosynthetic pathway and environment

Abstract: The ratio of deuterium to hydrogen (expressed as δD) in hydrogen released as water during the combustion of dried plant material was examined. The δD value (metabolic hydrogen) determined on plant materials grown under controlled conditions is correlated with pathways of photosynthetic carbon metabolism. C3 plants show mean δD values of-132‰ for shoots and -117‰ for roots; C4 plants show mean δD values of -91‰ for shoots and-77‰ for roots and CAM plants a δD value of-75‰ for roots and shoots. The difference be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
71
1

Year Published

1981
1981
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(82 citation statements)
references
References 16 publications
10
71
1
Order By: Relevance
“…1). In contrast, Ziegler et al (25) observed a correlation between AD and 6 3C values of total organic matter of CAM plants. The basis for the difference between these observations can be understood by considering the factors which …”
Section: Methodsmentioning
confidence: 83%
See 1 more Smart Citation
“…1). In contrast, Ziegler et al (25) observed a correlation between AD and 6 3C values of total organic matter of CAM plants. The basis for the difference between these observations can be understood by considering the factors which …”
Section: Methodsmentioning
confidence: 83%
“…2). Within the group of plants with 6'3C values ranging from -30%o to -25%o, there is a broad overlap in the oxygen isotope ratio among C3 plants having 680 Ziegler et al (25) proposed that CAM plants are enriched in deuterium relative to C3 and C4 plants because of their ability to maintain metabolic activity under water stress. They argued that, under water stress, plant water becomes enriched in deuterium during evaotranspiration (23), and this enrichment is passed on to the organically bound hydrogen.…”
Section: Methodsmentioning
confidence: 99%
“…Cyt involved in electron transport in either photosynthesis or respiration, or both (4,11 above that seen in the dark. The primary isotope fractionation may occur during the reduction of NADP during photosynthesis because, in the dark, reducing power is generated from different pathways, glucose 6-P dehydrogenase and the tricarboxylic acid cycle, without fractionating hydrogen isotopes.…”
Section: Methodsmentioning
confidence: 99%
“…Plants grown under controlled conditions show a reproducible and measurable discrimination (fractionation) of as much as 20o between the isotopes of hydrogen, deuterium (D), and protium (H) (1,11). Cultures of microalgae, natural populations of phytoplankton, macroalgae, mosses, and higher terrestrial plants all have lower concentrations of the heavy isotope of hydrogen (deuterium) than the environmental water.…”
mentioning
confidence: 99%
“…The patterns of diurnal variation (or lack thereof) in isotope ratios of plant water are consistent with the gross anatomical and physiological characteristics of the plants studied here. Our observations support the previously advanced hypothesis that high D/H ratios in cellulose nitrate prepared from CAM plants relative to those for C3 plants are not caused by greater deuterium enrichment in the water in CAM plants, but rather by isotopic fractionations associated with different biochemical reactions in the two types of plants.It is now well established that the stable isotopic composition of the nonexchangeable hydrogen in cellulose (measured as cellulose nitrate) is related to a plant's photosynthetic mode (7,8,11,13). Cellulose nitrate prepared from CAM plants has more deuterium than that from C4 and C3 plants that grew under the same climatic regime and used the same water source.…”
mentioning
confidence: 99%